Dual-energy CT in patients with abdominal malignant lymphoma: impact of noise-optimised virtual monoenergetic imaging on objective and subjective image quality. Issue 9 (September 2018) - Lenga, L.; Czwikla, R.; Wichmann, J.L.; Leithner, D.; Albrecht, M.H.; D'Angelo, T.; Arendt, C.T.; Booz, C.; Hammerstingl, R.; Vogl, T.J.; Martin, S.S.
Abstract : Aim: To investigate the impact of noise-optimised virtual monoenergetic imaging (VMI+) reconstructions on quantitative and qualitative image parameters in patients with malignant lymphoma at dual-energy computed tomography (DECT) examinations of the abdomen. Materials and methods: Thirty-five consecutive patients (mean age, 53.8±18.6 years; range, 21–82 years) with histologically proven malignant lymphoma of the abdomen were included retrospectively. Images were post-processed with standard linear blending (M_0.6), traditional VMI, and VMI+ technique at energy levels ranging from 40 to 100 keV in 10 keV increments. Signal-to-noise (SNR) and contrast-to-noise ratios (CNR) were objectively measured in lymphoma lesions. Image quality, lesion delineation, and image noise were rated subjectively by three blinded observers using five-point Likert scales. Results: Quantitative image quality parameters peaked at 40-keV VMI+ (SNR, 15.77±7.74; CNR, 18.27±8.04) with significant differences compared to standard linearly blended M_0.6 (SNR, 7.96±3.26; CNR, 13.55±3.47) and all traditional VMI series ( p <0.001). Qualitative image quality assessment revealed significantly superior ratings for image quality at 60-keV VMI+ (median, 5) in comparison with all other image series ( p <0.001). Assessment of lesion delineation showed the highest rating scores for 40-keV VMI+ series (median, 5), while lowest subjective image noise was found for 100-keV VMI+ reconstructions (median, 5). Conclusion: Low-keV VMI+ reconstructions led to improved image quality and lesion delineation of malignant lymphoma lesions compared to standard image reconstruction and traditional VMI at abdominal DECT examinations. Highlights: DECT allows for post-processing of noise-optimised VMI+. Low-keV VMI+ significantly improve image quality of malignant lymphomas. Highest SNR and CNR values were observed for 40-keV VMI+ series. 60-keV VMI+ showed highest scores regarding subjective image quality.